Formations of the Secular: By Talal Asad (Stanford: Stanford University Press, 2003. 269 pages.) (American Journal of Islam and Society, 2006)
This most interesting and ground-breaking study presents a Foucauldian andNietzschean genealogical tracing of the concept of the secular, workingback from the present to the contingencies that have coalesced to producecurrent certainties. It asks what an “anthropology of secularism” might looklike and examines the connection between the “secular” as an epistemic categoryand “secularism” as a political doctrine. Asad attempts to avoid thetrap of making pronouncements about secularism’s virtues and vices, irrespectiveof its origin, and to proffer instead an anthropological formulationof its doctrine and practice.According to the author, secularism is more than a mere separation ofreligious from secular institutions of government, for it presupposes newconcepts of religion, ethics, and politics; as well as the new imperativesassociated with them, and is closely linked to the emergence of the modernnation-state (pp. 1-2). In contrast to pre-modern mediations of nontranscendedlocal identities, secularism is a redefining, transcending, anddifferentiating political medium (representation of citizenship) of the self,articulated through class, gender, and religion (p. 5).Concomitantly, he questions the secular’s self-evident character evenwhen admitting the reality of its “presence” (p. 16). His main premise is that“the secular” is conceptually prior to the political doctrine of secularism, thesecular being that formation caused by a variety of concepts, practices, andsensibilities that have come together over time (p. 16). He concludes that the“secular” cannot be viewed as the “rational” successor to “religion,” butrather as a multilayered historical category related to the major premises ofmodernity, democracy, and human rights.Within the above introductory framework, the book’s seven chapters aredivided into three parts. The first part, comprising three chapters, explores theepistemic category of the secular. The following three chapters of part 2 ...